2002
DOI: 10.2175/106143002x140008
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Various Measures of Microbial Growth Kinetics in Suspended and Biofilm Cultures During Biodegradation of Naphthalene

Abstract: This research focused on measurement of bacterial growth rates and activities in suspended cultures and biofilms using Pseudomonas putida (ATCC 17484) for biodegradation of naphthalene. A comparison was made of the effect of three biomass measures: optical density, total cell protein, and living cell number on the calculated rate of naphthalene disappearance. Living cell number was determined by optimizing a fluorescent staining technique and using epifluorescence microscopy. All three techniques gave similar … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2003
2003
2012
2012

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 20 publications
0
3
0
1
Order By: Relevance
“…16 The reliability of such an approach has been confirmed by several authors. [17][18][19][20] In this study, total proteins content was determined using the Lowry method after alkaline hydrolysis (NaOH 1 N, 1 h at 80 °C) of biomass samples. 14 Biomass density.…”
Section: Measurement Methods and Calculation Proceduresmentioning
confidence: 99%
“…16 The reliability of such an approach has been confirmed by several authors. [17][18][19][20] In this study, total proteins content was determined using the Lowry method after alkaline hydrolysis (NaOH 1 N, 1 h at 80 °C) of biomass samples. 14 Biomass density.…”
Section: Measurement Methods and Calculation Proceduresmentioning
confidence: 99%
“…Using a Gauss-Newton nonlinear regression method, it was found that the Haldane model incorporating endogenous metabolic consumption best described the kinetics of the biological reactions in the systems studied. Optical density, total cell protein, and living cell number were measures in a study of bacterial growth rates and activities in suspended cultures and biofilms using Pseudomonas putida for degradation of naphthalene (Shim and Lewandowski, 2002). All three techniques gave similar results in terms of the specific growth rates, and the lag time observed between the disappearance of naphthalene and the growth of biomass was believed as a consequence of the production of intermediate products.…”
Section: Growth and Modelingmentioning
confidence: 99%
“…One reason inert biomass is sometimes ignored is because measurements of active or inert biomass are rather difficult (Shim and Lewandowski, 2002;Mitchell et al, 2004). Another possible reason is that a consideration of inert biomass would make model resolution and calculation more complicated.…”
Section: Introductionmentioning
confidence: 99%